Model Evaluasi Trayek Kapal Tol Laut Untuk Maluku dan Papua Bagian Selatan - Yunianto, Irwan Tri; Nur, Hasan Iqbal; Ardhi, Eka Wahyu; Adhitya, Bianca Prima (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2019)
Indonesia as an archipelago state requires having an adequate connectivity to improve the welfare and the economic balance. Tol Laut programme which has been started since 2016 is a government strategy designed to create connectivity among regions in Indonesia within regular and scheduled shipping especially to Eastern Indonesia and remote island. Tol Laut programme implementation which required the government evaluations is operationl ship planning. The following research is aimed to generate the most optimised ship route evaluation in terms of tol laut by conducting optimization method which is schemed through Multiport and Hub-Spoke trans-portation network. The most optimised tol laut shipping network through South Maluku and Papua (minimum Required Freight Rate (RFR)) is operating the Hub-Spoke operation where the hub port is in Saumlaki. Require-ment of fleets in order to support hub-spoke operational is that one unit of fleet with capacity 296 TEUs, three units of fleets with capacity 60 TEUs and one unit fleet with capacity 87 TEUs by having the potential for 50% subsidy savings compare to year 2018, cut down from IDR 119,21 billion to IDR 59,46 Billion.